2015
DOI: 10.1124/jpet.114.221788
|View full text |Cite
|
Sign up to set email alerts
|

PF-1355, a Mechanism-Based Myeloperoxidase Inhibitor, Prevents Immune Complex Vasculitis and Anti–Glomerular Basement Membrane Glomerulonephritis

Abstract: Small vessel vasculitis is a life-threatening condition and patients typically present with renal and pulmonary injury. Disease pathogenesis is associated with neutrophil accumulation, activation, and oxidative damage, the latter being driven in large part by myeloperoxidase (MPO), which generates hypochlorous acid among other oxidants. MPO has been associated with vasculitis, disseminated vascular inflammation typically involving pulmonary and renal microvasculature and often resulting in critical consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 48 publications
1
65
0
1
Order By: Relevance
“…Recently a number of direct specific MPO inhibitors have been developed. These include PF-1355 (2-(6-(2,5-dimethoxyphenyl)-4-oxo-2-thioxo-3,4-dihydropyrimidin-1(2H)-yl)acetamide) (Zheng et al, 2015) and MPOi-II (4-(5-fluoro-1H-indol-3-yl)butanamide) (Soubhye et al, 2013). As expected, both of these inhibitors dramatically reduced MPO activity in NB4 cells (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a number of direct specific MPO inhibitors have been developed. These include PF-1355 (2-(6-(2,5-dimethoxyphenyl)-4-oxo-2-thioxo-3,4-dihydropyrimidin-1(2H)-yl)acetamide) (Zheng et al, 2015) and MPOi-II (4-(5-fluoro-1H-indol-3-yl)butanamide) (Soubhye et al, 2013). As expected, both of these inhibitors dramatically reduced MPO activity in NB4 cells (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MPO has become a target of interest for novel anti-inflammatory drug development (Malle et al, 2007), and a number of potent specific MPO inhibitors were recently reported (Tidén et al, 2011; Forbes et al, 2013; Soubhye et al, 2013, 2016; Li et al, 2015; Zheng et al, 2015). We have used two such inhibitors, PF1355 and MPOi-II, and show that like SA, they reduce etoposide- and mitoxantrone-induced damage in MPO-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…MPO inhibitors, such as 4-aminobenzoic acid hydrazide 141 or PF-1355 (REF. 144), reduce NETosis, neutrophil recruitment and levels of circulating cytokines. PF-1355 treatment reduced neutrophil accumulation in a mouse model of immune complex-mediated vasculitis and suppressed albuminuria and chronic renal dysfunction in a murine model of anti-GBM-induced glomerulonephritis.…”
Section: Potential Therapeutic Modulation Of Netosismentioning
confidence: 99%
“…Therefore, MPO is considered a druggable target with small-molecule inhibitors already identified and more expected for limiting ROS/RNS production. In preclinical study, several MPO inhibitors have limited inflammation in diseases, including thioxanthine-2 in chronic obstructive pulmonary disease studies [15], PF-1355 in vasculitis and glomerulonephritis [24], and INV315 in atherosclerosis [25]. In this review, we will mainly discuss the recent, emerging tools for in vivo assessment of MPO as a target with the goal of monitoring disease progression, tracking PMN migration, and detecting inflammatory sites for preclinical or clinical applications.…”
Section: Physiologic Importance Of Mpo Functionmentioning
confidence: 99%